PENERAPAN PENDEKATAN KOMUNIKATIF (COMMUNICATIVE APPROACH) DENGAN SOSIODRAMA DAN INTERVIEW UNTUK MENINGKATKAN KEMAMPUAN BERBICARA DALAM PEMBELAJARAN KAIWA (PERCAKAPAN BAHASA JEPANG) - Nessa Agnesia, - (2020)
This research is based on student difficulty in speaking Japanese. Considering speaking Japanese (kaiwa) in learning Japanese is one of the important things, therefore, an appropriately approach is needed to facilitate students in speaking Japanese. The purpose of this study is to describe the ability to speak Japanese with a Communicative Approach with Sociodrama and Interview, ability to speak with the Translation Method, differences in speaking skills using the Communicative Approach with Sociodrama and Interview and Translation Methods, and the quality of the Communicative Approach with Sociodrama and Interview according to students' opinions in kaiwa learning, The research method is a quantitative experimental method, with Pretest-Posttest Control Group Design. The sample of this study were participants of the Class C LPK Minori course of 2019 academic year. The instruments used were tests and questionnaires. Finding shows that the participant speaking skill is higher in course using the Communicative Approach with Sociodrama and Interview than students used the Translation Method. This finding is supported by questionnaire result indicating that most students consider Kaiwa learning by using the Communicative Approach with Sociodrama and Interview very interesting and can improve their Japanese language skills. Keywords: Japanese, kaiwa, communicative.